Comparison of usability and ergonomic risks of using a laptop and tablet computers for online learning: A field experimental study. - Butmee, Totsapon; Ponlamuang, Pattarapong; On-Sri, Tanatorn; Phomseranee, Anittha (Work, 2026)
Background: In recent decades, electronic devices have been used increasingly for many purposes such as studying and working. Objective: This research aimed to investigate and compare the usability, cognitive workload, and ergonomic postural risks of using laptops and tablets for online learning. Methods: This research involved 30 students, 86.75% female and 13.25% male, who were randomly assigned to study online via either laptops (15 students) or tablets (15 students). Instruments used to collect data were the general information questionnaire, Rapid Upper Limb Assessment (RULA), Mental Workload Index assessment (NASA-TLX), and System Usability Scale (SUS). The SUS, NASA-TLX, and RULA scores were compared by using Independent t-test and Mann-Whitney U test. Results: Findings showed that a significant portion of the students (83.3%) spent more than eight hours per day using electronic devices. The analysis of the comparison between these two groups of students revealed significant statistical differences (at the 0.05 level) in the usability and ergonomic postural risks of laptops and tablets. However, no significant differences in cognitive workload were found. Conclusions: Besides serving as a guideline for designing online education management, the findings of this study can also be applied in the workplace, such as working, meeting, training and controlling machinery through computer devices. Recommendations for further study include exploring more difficult academic lessons, and other tasks such as different kinds of work. In addition, authorities regulating online learning and working through electronic devices should mandate that learners or online workers select appropriate devices for user health and efficiency.